Hybrid education in Latin American universities 2020-2023: a narrative review - Bustillos-Cotrado, Jose A. (2023)
Hybrid education had a great impact on the formative process of university students, considered as an educational modality with a great apogee during and after the health crisis produced by the Covid-19 pandemic. The objective of the study is to know formative experiences of hybrid education in Latin American universities. The methodology used was a narrative review of scientific publications indexed in the Scielo and Google Scholar databases, during the period 2020-2023, according to the search and eligibility strategies. In the collection of information, a total of 324 scientific publications were initially found; the titles and abstracts of each one were reviewed, thus selecting 65 and discarding 51; 14 studies that met the selection criteria were included. Therefore, it is concluded that the exercise and role of university teachers in the Latin American context is optimistic and challenging, due to the technological and pedagogical demands of hybrid learning models. As well as the development of digital competencies of the university community and the availability of technological infrastructure according to the needs and possibilities of each institution.